Pemanfaatan Media Pembelajaran Berbasis Internet pada Konsep Sistem Peredaran Darah Terhadap Hasil Belajar Kognitif Siswa pada SMA Negeri 1 Woyla - Taufik Hidayat; Hafnati Rahmatan; Khairil Khairil (Biotik, 2016)
Internet based – learning media is one of the learning sources that can be used to replace the text book. This research was aimed to find out the difference of learning result of students who utilized internet based – learning media as the sources of learning compare to the students who used conventional learning method on the topic of blood circulatory system. An experimental research had been conducted at SMAN 1 Woyla in the school year of 2014/2015. The population of this research was 60 students, which were 30 students of XII IPA 1 and 30 students of XII IPA 2 class. The entire population was chosen as the samples of the research which were 30 students for experimental class and 30 students for control class. The data were collected by using pre-test and post-test. The data were analyzed by using independent sample t-tes or Mann Whitney test. The results showed that: (1) the N-Gain mean value of experimental class was 60 which was categorized as medium and for the control was 20 which was categorized as low, (2) the learning result was significantly different between the students who used internet based – learning media and the students who were taught conventionally on the topic of blood circulatory system with P value of 0,000 < 0,05. It can be summarized that there was a significant difference of learning result of students who used internet based – learning media with the students who used conventional learning method especially on the topic of blood circulatory system.